Short and longer-term outcomes for women and their children according to planned mode of birth after previous caesarean section - Fitzpatrick, K (2021)
Background: Policy supports offering pregnant women with previous caesarean section a choice between elective repeat caesarean section (ERCS) or planning a vaginal birth after previous caesarean (VBAC), provided they have no contraindications to VBAC. However, robust comprehensive information on the associated outcomes to counsel women is lacking. This thesis investigated short and longer-term outcomes for women and their children according to planned mode of birth after previous caesarean section (CS).